The effect of cooperative learning on improving the performance level of some sport skills for 11th eleventh grade students in Muscat Governorate - Al-Defaye, Dawod Amer; Al-Kitani, Mahfoodha Sulaiman; Al-Rawahi, Naser Yasser (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effect of cooperative learning on improving the level of performance of some sport skills prescribed for eleventh grade students in Muscat Governorate. The sample of the study was chosen randomly from the eleventh-grade students. Where two divisions were chosen out of (13) divisions in the school, one representing the experimental group with (27) students, and the other the control group with (25) students, thus the number of the basic sample was (52) students. The program was applied for a period of (5) weeks, at the rate of (4) educational units per week, the time of each unit was (45) minutes. The most important results indicated that the learning style (cooperative - traditional) had a positive effect on learning the sports skills under study, except for the crushing hit in volleyball. In addition, the experimental group showed better performance than the control group in passing skills, hook shot in basketball and the skill of shooting from the side fall in handball. The researchers recommended conducting similar studies on other skills to find out the importance of the cooperative learning method in teaching group games skills in the physical education curricula.
Keywords: Learning skill; Physical Education; Sport skills; Games; Students